Commodity Market Review 1998-99 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
FAO. 104 pp.ISBN 925 104276 4.$16.00 Euro 15.40FAO Sales and Marketing Group,Viale delle Terme di Caracalla, 00100 Rome, Italy.Fax: + 39 06 57 05 33 60Email: publications-sales@fao.org